Media Narratives in the Israel-Palestine Conflict: A Constructivist Approach to Analyzing Media Bias and Digital Activism - Taufiq, Fariz Tsabit; Alam, Gilang Nur; Dermawan, Windy (Universitas Padjadjaran, 2025)
The Israel-Palestine conflict, one of the most complex and protracted international disputes, has been profoundly shaped by media representations that influence public opinion and international relations. This study identifies three key factors shaping narratives through mainstream and social media: (i) Western mainstream media bias favoring Israel, (ii) the use of emotional language and selective reporting, and (iii) the rise of social media activism, exemplified by campaigns such as “All Eyes on Rafah”, which amplify marginalized Palestinian voices. Using a qualitative descriptive approach based on Creswell’s framework, the research explores the existence and interaction of these factors in shaping media roles. The study highlights the dynamic interplay between media narratives, public opinion, and foreign policy-making, shaped by historical context, social values, and norms. Findings reveal that while mainstream media historically demonstrate bias and selective framing, social media platforms create space for counter-narratives and more diverse perspectives. This analysis provides deeper insight into how these three factors collectively construct media discourse and potentially influence global public opinion and policy responses to the Israel-Palestine conflict. Konflik Israel-Palestina, sebagai salah satu sengketa internasional paling kompleks dan berkepanjangan, sangat dipengaruhi oleh representasi media yang membentuk opini publik dan hubungan internasional. Penelitian ini mengidentifikasi tiga faktor utama yang memengaruhi narasi melalui media arus utama dan media sosial: (i) bias media arus utama Barat yang cenderung mendukung Israel, (ii) penggunaan bahasa emosional dan pelaporan yang selektif, serta (iii) munculnya aktivisme media sosial yang dicontohkan oleh kampanye “All Eyes on Rafah” yang memperkuat suara-suara Palestina yang termarginalkan. Dengan menggunakan pendekatan deskriptif kualitatif berdasarkan kerangka Creswell, penelitian ini menelaah keberadaan dan interaksi ketiga faktor tersebut dalam membentuk peran media. Studi ini menekankan interaksi dinamis antara narasi media, opini publik, dan pembuatan kebijakan luar negeri yang dipengaruhi konteks historis, nilai sosial, dan norma. Temuan menunjukkan bahwa meskipun media arus utama secara historis menampilkan bias dan pembingkaian selektif, media sosial menyediakan ruang bagi narasi tandingan dan perspektif yang lebih beragam. Analisis ini memberikan pemahaman yang lebih mendalam mengenai bagaimana ketiga faktor tersebut secara kolektif membentuk wacana media serta berpotensi memengaruhi opini publik global dan respons kebijakan terhadap konflik Israel-Palestina.